OPPORTUNITIES FOR IMPROVING THE MANAGEMENT SYSTEM OF THE EDUCATIONAL INSTITUTION WITH INFORMATION TECHNOLOGIES - Mardonov Obidjon Omonovich (Journal of Higher Education and Academic Advancement, 2024)
In recent years, the education system has been fundamentally reformed in our country, and special attention is being paid to raising a mature generation who are worthy successors of our tomorrow. The implementation of such ambitious tasks places a great responsibility on the centers of retraining of preschool and school education workers and their professional development.